73° Congresso dell'Unione Zoologica Italiana Firenze 24 -27 Settembre 2012 Riassunti dei contributi - Baistrocchi, Elena; zaccaroni, marco (Proceedings e report, 2013)
This volume collects the contributions to the 73rd Congress of the Italian Zoological Union, held in Florence in September 2012, and organised together with the "Leo Pardi" Department of Evolutionary Biology. The Congress, to which many zoologists, comparative anatomists, reproductive biologists, ethologists and ecologists participated, opened with a plenary reading by Marlene Zuk, from the University of Minnesota, entitled "Mate choice and thinkering with evolution". The Congress was then divided into four symposia: I "From sexual strategies to social behaviour (in honour of Tullia Zetto)"; II "Use of space, orientation and migration (in honour of Guido Tosi)"; III "Endocrine destroyers"; IV "Allochthonous species". The Symposia were enriched by the reports made upon request by Paolo Luschi, Gian Carlo Panzica and Piero Genovesi.